1946
DOI: 10.1001/archneurpsyc.1946.02300150086006
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Erosion of the Base of the Skull From a Leptomeningeal Cyst

Abstract: EROSION of the cranial bones from pressure of a leptomeningeal cyst is an uncommon, but not rare, condition. While the majority of such cysts develop after severe trauma to the skull, usually with fracture, there is evidence that congenital abnormalities in the dura and leptomeninges may contribute to their production. Haymaker and Foster1 reported a case in which a large collection of clear, colorless fluid resembling cerebrospinal fluid was found enclosed between the two layers of the dura in the posterior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Except for one, all of our patients were 3 years old or younger. However, several cases of GSF have been reported in adults [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Except for one, all of our patients were 3 years old or younger. However, several cases of GSF have been reported in adults [11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Psammoma bodies are as well scattered in the arachnoid mater as in the glomus choroideum (Shuangshoti and Netsky, 1970). The mode of formation of these calcospherites has been debated, but it has been suggested that they are related to the calcification occurring in degenerated meningocytic whorls (Shuangshoti and Netsky, 1970 (Soule and Whitcomb, 1946;Taveras and Ranshoff, 1953;Starkman et al, 1958). Moreover, an old subdural haematoma may become cystic especially when the large clot is partly absorbed; a subdural cyst with inner and outer neomembranes is formed and may be calcified (Merritt, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Cyst of the arachnoid may be congenital or acquired. The acquired arachnoid cysts may occur after cranial trauma, intracranial haemorrhage, or inflammation which result in localised entrapment of the CSF because of adhesions between the pia mater and arachnoid mater, or are related to herniation of the arachnoid mater through dural or cranial defects (Soule and Whitcomb, 1946;Taveras and Ranshoff, 1953;Starkman et al, 1958). Moreover, an old subdural haematoma may become cystic especially when the large clot is partly absorbed; a subdural cyst with inner and outer neomembranes is formed and may be calcified (Merritt, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…According to their apparent location in the subdural or subarachnoid spaces and possible aetiology (focal inflammatory processes, congenital anomalies, trauma of meninges), these fluid-filled cavities or cysts, usually walled off by arachnoidal adhesions, have been described by Abbott (1933), Claude (1933), Okonek (1938), Soule and Whitcomb (1946), Taveras and Rouschoff (1953), and Zehnder (1938) under a variety of terms.…”
mentioning
confidence: 99%